Maritime Security in the Region: SCS and ECS as Key Arenas for Converging Political Interests. (2nd July 2016) - Koda, Yoji
Abstract : This article examines the situations in the South China Sea (SCS) and East China Sea (ECS) and the reasons for recent political and strategic attention. As background it reviews the history of maritime activities in Asia where there was no real maritime Great Power with continuity. It then discusses the latest situations in the ECS around the Senkaku Islands, where China's Coast Guard vessels and fishing boats have made occasional incursions into Japanese waters, and the relatively-less understood Scarborough Shoal and the Pratas Islands in the SCS that have strategic significance in a future powerbalance in the SCS. The article then notes the US rebalance to Asia and the interpretation of the principle of Freedom of Navigation. It continues with the strategic and diplomatic measures and operational and tactical measures that Japan should take. It concludes noting that Japan and the US must prepare a wide range of measures in advance to regain and maintain maritime security and stability.